Diversidade e bioprospecção de fungos presentes em lagos Antárticos - Vívian Nicolau Gonçalves (2011)
In Antarctic continent, lakes are the most favorable habitats for the growth of extremophile microorganisms, which can be important sources of bioactive metabolites. Several studies have been performed to evaluate the diversity of fungi isolated from different substrates of Antarctica. However, few studies have been performed to assess the diversity of fungi present in the water lakes and the ability of these microorganisms to produce secondary metabolites with biological activity. The aim of this study was to collect water samples from six Antarctic lakes of Admiralty Bay, at King George Island (lakes Stenhouse, Macchu Picchu, Refuge II, Agat and Wanda) and Deception Island (Crater Lake) in Antarctica for the isolation of fungi. Besides that, it was evaluated the ability of these microorganisms to produce secondary metabolites with antifungal, antitumor and antiparasitic activities. A hundred and eight filamentous fungi were obtained from 90 water samples. The fungal isolates were grouped into 99 distinct morphotypes according to their macroscopic characteristics of their colonies, and one isolate of each group was then selected to molecular identification by sequencing the internal transcribed spacer (ITS) region of rRNA gene. Seveteen and a half percent of the taxa obtained in the lakes sampled are endemic species and belong to the genera: Antarctomyces, Cadophora, Cladosporium, Cosmospora, Davidiella, Fontanospora, Geomyces, Gibberella, Helgardia, Microdochium, Penicillium, Phaeosphaeria, Phoma, Pseudeurotium, Thelebolus and Trichoderma. The species Geomyces pannorum (13.5% of the total isolates) was predominant and the highest number of isolates was obtained from Lake Stenhouse (26%), which showed the highest diversity showed by the Shannon and Simpson indices. The similarity of the fungal community of the lakes Macchu Picchu/Wanda and Refúgio II/Wanda, estimated by the coefficient of Sorensen (QS) and Bray-Curtis were more similar than the others. The different similarity values assigned to the lakes sampled may be due to the different physical and chemical characteristics found in the different ecosystems studied. Two hundred and twenty methanolic extracts were obtained [58% of filamentous fungi and 42% of Antarctic yeasts isolated by Brandão (2010)]. The extracts were tested at the concentration of 250μg/mL for their capacity to inhibit the growth of opportunistc strains of Candida albicans (ATCC 18804, and 15.3C 2.1A) and the pathogenic fungus Paracoccidioides brasiliensis (Pb18). The extracts were also tested at the concentration of 20μg/mL for their capacity to inhibit cells of Leishmania amazonenis and cell lines of human tumor (TK-10 and MCF-7). In the bioassays against strains of C. albicans, 19 (8.64%) extracts of the fungi were considered promising (inhibitory activity ≥ 70%). Most of the extracts considered promising and moderately promising (inhibitory activity between 50 and 69%) inhibited the strain of C. albicans 2.1A, resistant to itraconazole. In the bioassays against the fungus P. brasiliensis, 14 extracts (8.2%) were considered promising. From all extracts tested on the bioassays with all microrganisms and target cells, 31 were considered active, being most obtained from filamentous fungi. The highest numbers of promising extracts were obtained from filamentous fungi of Stenhouse lake. The yeasts that showed activity against P. brasiliensis were Rhodotorula sp., Exophiala heteromorpha and Cryptococcus victoriae. The filamentous fungi that showed biological activity were distributed among the genera Antarctomyces, Cadophora, Cladosporium, Geomyces, Microdochium, Mortierella, Penicillium, Pseudeurotium and Thelebolus. G. pannorum was the species with largest number of extracts with biological activity (19.4%)against at least one microorganism or target cell. None of the extracts were able to inhibit the cells of L. amazonenis. The taxa Leucosporidiella muscorum and Penicillium sp. showed activity on tumor cell lines. The results of this research showed the importance of studies about diversity and bioprospecting of fungi in Antarctic lakes. It is been also suggested that environment represent a rich source for the isolation of strains producing bioactive metabolites that can have the potential to develop antifungal and antitumor drugs.